Facile C–H bond activation on a transient gallium imide. Issue 49 (31st May 2022) - Kassymbek, Aishabibi; Spasyuk, Denis; Dmitrienko, Anton; Pilkington, Melanie; Nikonov, Georgii I.
Abstract : In situ imidation of the Ga(i ) compound 1 by azide N3 SiMe3 results in transient monomeric imide NacNacGaNSiMe3 amenable to C–H bond activation of a variety of substrates featuring hard donor sites. Abstract : Reaction of NacNacGa with azide N3 SiMe3 results in the generation of a transient imide NacNacGa(NSiMe3 ) that can cleave unactivated sp 3 C–H and sp 2 C–H bonds of different substrates, affording gallium amides. Pyridine, cyclohexanone, ethyl acetate, DMSO, and triethylphosphine oxide were activated in this process producing corresponding gallium amides. All new compounds were characterised by multinuclear NMR and X-ray diffraction.